Real and Financial Integration in Europe - Evidence for the Accession States and for the Pre-Ins - Claudia M. Buch; Jörg Döpke (Kiel Institute of World Economics (IfW), 1999)
The process of European integration has gained considerable momentum during the past couple of years. This paper provides an assessment of the degree of integration of both the accession states of central and eastern Europe and of the pre-ins for monetary union with respect to Germany. Using tests for cointegration and common features for monthly data during the 1990s, we find evidence for financial rather than real integration.
Keywords: C32; E32; F36; 330; European integration; accession states; European Monetary Union; common feature tests; cointegration; Wirtschaftsunion; EU-Erweiterung; Marktintegration; Europäische Wirtschafts- und Währungsunion; Kointegration; Schätzung; Deutschland; Tschechische Republik; Estland; Ungarn; Polen; Slowakei; Dänemark; Schweden; Großbritannien